Analisis Peran Unit Terminal Inspection Service dalam Pelaksanaan Pengawasan Fasilitas Landside di Bandar Udara Internasional Minangkabau Padang - Rafli Aditya Rahman; Sundoro Sundoro; Yenni Arnas (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
This study aims to analyze the role of the Terminal Inspection Service (TIS) Unit in supervising landside facilities at Minangkabau International Airport. Landside facilities include passenger terminals, drop-off areas, parking lots, and other public spaces that serve as key interaction points between airport services and users. Effective supervision of these areas is essential to ensure safety, comfort, and order within the airport environment. A qualitative descriptive approach was employed in this research, with data collected through field observations, in-depth interviews with TIS personnel and related stakeholders, as well as documentation analysis of existing regulations and supervision procedures.The findings reveal that the TIS Unit plays a strategic role in maintaining service quality and the security of landside facilities. This role is carried out through regular monitoring activities, early detection of potential disruptions, and the handling of various violations in public areas. However, the implementation of TIS duties still faces several challenges. These include limited personnel, which restricts comprehensive supervision of all areas; slow response from relevant units when operational issues are reported; and low discipline and compliance among service users, which further complicates enforcement efforts.To enhance the effectiveness of supervision, this study proposes several recommendations. These include strengthening inter-unit coordination within the airport, providing ongoing training for TIS personnel to improve competency and responsiveness, and implementing an integrated digital reporting system to streamline reporting and follow-up processes. Such measures are expected to support more optimal and sustainable supervision of landside facilities at the airport.